INVESTING IN SYSTEMS DIGITAL FINANCE IN PERSPECTIVES ON ISLAMIC LAW STUDIES CASE: SYSTEM ONLINE LOANS - Parsih, Feli; Hasan, Asyari (istinbath, 2024)
This research aims to determine the number of cases of illegal businesses imitating licensed entity websites as if the website officially belonged to the licensed entity. Therefore, one way to protect potential investors from illegal businesses is to find out whether the company is registered with the Financial Services Authority (OJK) or not. Therefore, this article examines sharia investment options to avoid illegal business. This study uses a descriptive-qualitative approach to study literature. Additionally, all the data collected will likely be essential to what is being researched. Thus, the research report will contain quotations and data processing to provide an overview of the report's presentation. The results of this research are several Sharia investment instruments that have been registered with the OJK to avoid fraudulent investments, including Sharia stock investments, Sharia mutual fund investments, Sharia deposits, retail sukuk, and gold.